Randomised controlled trial of mesh fixation with nonabsorbable versus delayed absorbable suture in open inguinal hernia patients undergoing open inguinal hernioplasty in tertiary health center of Ahmedabad - Divya Jyoti Banerjee; Zil Desai; Debabrata Maity (International Surgery Journal, 2026)
Background: Inguinal hernia repair is a globally frequent surgical procedure. The Lichtenstein tension-free hernioplasty is highly effective, yet the optimal suture material non-absorbable versus delayed absorbable for mesh fixation remains debated regarding its impact on postoperative pain and complications. Methods: A prospective, single-center, randomized controlled trial was conducted on 200 adult patients with primary inguinal hernias. Patients were randomized to undergo open Lichtenstein hernioplasty using either 2-0 polypropylene (non-absorbable, n=100) or 2-0 polyglactin (delayed absorbable, n=100) sutures. Postoperative pain (visual analog scale), recurrence rates, hospital stay, and complications were evaluated over a 6-month follow-up. Results: Postoperative pain scores showed no statistically significant difference between the polypropylene and polyglactin groups at any time point up to 6 months. The incidence of complications, including wound infection, local swelling, seroma, and recurrence, was comparable across both groups. Duration of hospital stay was also similar. Conclusion: Delayed absorbable polyglactin sutures provide a safe and effective alternative to non-absorbable polypropylene sutures for mesh fixation in open Lichtenstein inguinal hernioplasty, offering comparable short-term outcomes in pain and complication rates.